A catalog of high-impact windstorms in Switzerland since 1859 - P. Stucki; S. Brönnimann; O. Martius; C. Welker; M. Imhof; N. von Wattenwyl; N. Philipp (Natural Hazards and Earth System Sciences, 2014)
In recent decades, extremely hazardous windstorms have caused enormous losses to buildings, infrastructure and forests in Switzerland. This has increased societal and scientific interest in the intensity and frequency of historical high-impact storms. However, high-resolution wind data and damage statistics mostly span recent decades only. For this study, we collected quantitative (e.g., volumes of windfall timber, losses relating to buildings) and descriptive (e.g., forestry or insurance reports) information on the impact of historical windstorms. To define windstorm severity, normalized and declustered quantitative data were processed by extreme value statistics. Descriptive information was classified using a conceptual guideline. Validation with independent damage information, as well as comparison with wind measurements and a reanalysis, indicates that the most hazardous winter storms are captured, while too few moderate windstorms are detected. Strong storms in the wind measurements and reanalysis are thus added to the catalog. The final catalog encompasses approximately 240 high-impact windstorms in Switzerland since 1859. It features three robust severity classes and contains eight extreme windstorms. Evidence of high winter storm activity in the early and late 20th century compared to the mid-20th century in both damage and wind data indicates a co-variability of hazard and related damage on decadal timescales.